Gender and sourcing in student journalism from Australia and New Zealand. Issue 2 (1st November 2021) - Shine, Kathryn
Although the proportion of female reporters has increased in almost all regions across the world in recent decades, news content continues to be dominated by male voices. Numerous studies from around the world have found that men generally comprise about 70 per cent of people quoted in news coverage. To date, these studies have focused on mainstream media coverage by established journalists. This article contributes to the existing literature by providing an analysis of student journalism from the Australian aggregated news site, The Junction. The analysis considered the gender of sources quoted, the function of the female sources and the inclusion of gender equality issues in the coverage. Overall, the student journalism was found to include a better gender balance, with females comprising about 44 per cent of overall sources and 46 per cent of expert sources. However, gender equality was the subject of very few stories, and almost all of these were all produced by female students. These findings are considered in relation to a growing body of research calling for gender education to be made compulsory for journalism students.